1999
DOI: 10.1046/j.1365-2230.1999.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

An infective aetiology for vulval lichen sclerosus re-addressed

Abstract: Although there is evidence to support an autoimmune basis for lichen sclerosus, there have also been some studies which suggest an infective aetiology. These include reports of the presence of spirochaetal forms with Steiner silver stains and purplish coccoid forms with Fite stains. We have repeated these studies on vulval biopsies obtained from 16 patients with vulval lichen sclerosus. Using the Steiner silver method we found no evidence of spirochaetal forms in any of the specimens. With the Fite stain we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Cantwell, using Fite stain, reported that, purplish cocco‐bacillary forms could be seen in six patients with generalized scleroderma, 10 patients with morphoea and four with lichen sclerosus; these cocco‐bacillary forms were interpreted as variably acid‐fast bacilli 20 . However, others have not confirmed this; we repeated this work, staining 16 specimens of lichen sclerosus with Fite stain and, although the majority of specimens did demonstrate purplish cocco‐bacillary forms, these also stained strongly with Toluidine blue suggesting that they were mast cells 21 …”
Section: Discussionmentioning
confidence: 87%
“…Cantwell, using Fite stain, reported that, purplish cocco‐bacillary forms could be seen in six patients with generalized scleroderma, 10 patients with morphoea and four with lichen sclerosus; these cocco‐bacillary forms were interpreted as variably acid‐fast bacilli 20 . However, others have not confirmed this; we repeated this work, staining 16 specimens of lichen sclerosus with Fite stain and, although the majority of specimens did demonstrate purplish cocco‐bacillary forms, these also stained strongly with Toluidine blue suggesting that they were mast cells 21 …”
Section: Discussionmentioning
confidence: 87%
“…However, a study (Farrell et al 1997) using vulval tissue has shown no spirochaetal forms, and coccoid bodies that were seen appeared to be mast cells rather than bacilli.…”
Section: Aetiologymentioning
confidence: 91%
“…One study showed that 12% of more than 1000 patients with lichen sclerosus had a positive family history 22 . An infective trigger has been suggested, based on an association with the bacteria Borrelia burgdorferi in Europe, but not in the United States 23,24 ; this may be one of many environmental triggers for lichen sclerosus in genetically susceptible individuals 25 . Studies show an increased incidence of basement membrane zone antigens and autoantibodies to extracellular matrix proteins in patients with lichen sclerosus 26,27 .…”
Section: Lichen Sclerosusmentioning
confidence: 99%